Does Time Matter? Identifying Levels of Community College Student Engagement Based on Length of Instructor-Created Videos in Online Classes - Morgan, Patrice; Kaplan, Vladyslava; Kirshner, Amanda (Advances in Social Sciences Research Journal, 2022)
With the rising popularity of online classes in higher education, keeping students engaged and developing effective methods of delivering content has become more challenging. One of the most used teaching and learning tools in online education is instructor-created videos. Various studies show that the majority of students favorably view the integration of instructor-created video content in online courses. Speculation continues to remain about how to effectively design video lessons to maximize their efficiency and increase the level of student engagement and overall academic performance. The current study examines students’ perceptions of instructor-created videos, with an emphasis on the preferred length of the videos. Google survey forms were created and distributed among students who are enrolled in Behavioral Science courses. The survey was completed by a diverse group of 159 online students. Participants were asked to identify academic engagement in their own words and share their personal experience with online classes, as well as answer more specific questions such as if instructor-created videos were used in the course, how long they were, and if the length of the videos determined whether students watched them or not. Findings indicated that while students prefer shorter videos, they would watch longer video lectures as long as they were required for the grade. The majority of responders found the use of instructor-created videos in the course helpful. These findings will allow researchers to offer the faculty a recommendation for the future effective use of instructor-created videos in online courses.